Gap junction hemichannels contribute to the generation of diarrhoea during infectious enteric disease. Issue 2 (14th October 2009) - Guttman, Julian Andrew; En-Ju Lin, Ann; Li, Yuling; Bechberger, John; Naus, Christian C; Vogl, A Wayne; Finlay, B Brett
Abstract : Objective: The attaching and effacing (A/E) pathogens enterohaemorrhagic Escherichia coli, enteropathogenic E coli and Citrobacter rodentium colonise intestinal tracts, attach to enterocytes, collapse infected cell microvilli and alter numerous host cell processes during infection. Enterocyte alterations result in numerous small molecules being released from host cells that likely contribute to diarrhoeal phenotypes observed during these infections. One possible route for small molecules to be released from intestinal cells may be through functional gap junction hemichannels. Here we examine the involvement of these hemichannels during the diarrhoeal disease caused by A/E pathogens in vivo. Design: Mice were infected with the diarrhoea-causing murine A/E pathogen C rodentium for 7 days. Connexin43 (Cx43) protein levels and immunolocalisation in the colon were initially used to determine alterations during A/E bacterial infections in vivo. Connexin mimetic peptides and connexin permeable tracer molecules were used to gage the presence and function of unpaired connexin hemichannels. The role of Cx43 in diarrhoea generation was assessed by comparing infections of wild-type mice to Cx43 mutant mice and determining the water abundance in the colonic luminal material. Results: We demonstrate that Cx43 protein levels are increased in colonocytes during in vivo A/E bacterial infections, resulting in functionally open connexon hemichannels in apical membranes of infected cells. Moreover, infected Cx43 +/− mice do not suffer from diarrhoeal disease. Conclusions: This study provides the first evidence that functional connexon hemichannels can occur in the intestine and are a novel molecular mechanism of water release during infectious diarrhoea.